Photonic Crystals: Topology‐Optimized 3D Photonic Structures with Maximal Omnidirectional Bandgaps (Adv. Theory Simul. 12/2018). Issue 12 (4th December 2018) - Meng, Fei; Jia, Baohua; Huang, Xiaodong
Abstract : 3D photonic crystals are critical for diverse engineering applications, but there are widespread challenges in intuitively designing their complex structures. In article number1800122, Xiaodong Huang and co‐workers utilize computer modelling and intelligent topology optimization, to systematically create 3D photonic structures with on‐demand broad omnidirectional bandgaps. The findings expand the existing knowledge on the geometrical characteristics of photonic bandgap crystals.